Pengembangan instrumen penilaian karakter siswa berdasarkan ajaran Nang (Menang) - Sri Purwanti Hidayati; Yuli Prihatni; Dita Surwanti (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to produce instruments for evaluating student character based on valid and reliable teaching evaluating the character of students of SMP Negeri 2 Kaliangkrik, Magelang Regency, and to find out what are the indicators in measuring student character based on the teaching of Nang (win) in State Junior High School 2 Kaliangkrik. The research design used is Research and Development with Borg and Gall models. The stages are research and information gathering, planning, initial product development, initial field testing, product revision, field testing, operational product revision, operational field testing, final product revision, and dissemination and implementation. The research subjects were 273 students of SMP Negeri 2 Kaliangkrik. Data collection techniques in the form of questionnaire research and instruments produced were questionnaire sheets. The assessment instruments that have been developed are validated by the expert and revised according to the advice of the expert. The data analysis technique used in this study is the validity test using factor analysis and reliability testing. The results of this study are arranged as a valid and reliable character evaluation instrument (win). Based on the development of the Nang character assessment instrument for students at Kaliangkrik State Junior High School 2 Kaliangkrik Magelang, what has been done has obtained a standardized instrument to measure the value of the character and ( win) with 11 indicators, namely (1) Not Easy Emotions and self-introspection (2) Increasing friends and study hard (3) Always tolerant. (4) Arrogant and humble (5) See things positively and dare to apologize and forgive (6) Be optimistic in all situations (7) Sportive (8) Do not Procrastinate and believe in yourself (9) No demeaning others and never give up (10) Always think clearly. (11) Appreciating Achievement.